Determinant of Timely First-shot Hepatitis B Immunization in East Lombok, West Nusa Tenggara, Indonesia - Machmud, Putri Bungsu; Gayatri, Dwi; Miko Wahyono, Tri Yunis (Jurnal Epidemiologi Kesehatan Indonesia, 2017)
Hepatitis B remains as one of health problems in the world. The results of several studies related to factors in predicting of the timely first-shot hepatitis B immunization were still inconsistent. Aim of this study is to identify determinant factors of the timely first-shot hepatitis B immunization in East Lombok, Indonesia. We used a cross sectional design study, and data derived from immunization coverage survey at six districts/ cities in 2013. A Total of 227 children aged 12 to 23 months who already got immunization of a first-shot hepatitis B vaccineand well documented were included as samples in this study. Timely first-shot hepatitis B immunization was defined as the first-shot of hepatitis B immunization within 24 hours after birth. Data were analyzed by using a logistic regression analysis. The result of this study showed only 60.4% of infants who got the timely first-shot hepatitis B immunization. Mother’s behavior was the only factor that had a statistically association with the timely first-shot hepatitis B immunization (P-value 0.007 CI 95% 1.94-3.62). Meanwhile, other factors i.e. sex, socio-economic status, parent’s education, knowledge and attitude of mother and place of immunization service had no statistically association with the first-shot of hepatitis B immunization